Animalia [videorecording (DVD)] - Leigh, Katie; Anderson, Brooke, 1981-; Hobbs, Christopher; Higgins, Kate; Johnson, Peta; Klein, Robert Mark; O'Gorman, Dean; Scott, David; Burnett, Ewan; Pope, Murray; Base, Graeme (Porchlight Home Entertainment, 2008)
Join 11 year-olds Zoe and Alex on a thrilling, beautifully animated adventure, as they are swept from their local library into Animalia, a unique world of speaking animals!